Hydroxychloroquine reduces hypertension and soluble fms-like kinase-1 in a Nω-nitro-l-arginine methyl ester-induced preeclampsia rat model. Issue 12 (26th December 2022) - Choi, Minji; Hwang, Jae Ryoung; Sung, Ji-Hee; Byun, Nagyeong; Seok, Ye Seon; Cho, Geum Joon; Choi, Suk-Joo; Kim, Jung-Sun; Oh, Soo-young; Roh, Cheong-Rae
Abstract : Objective: Hydroxychloroquine, a drug used for malaria and autoimmune diseases reportedly has beneficial effects against preeclampsia in pregnant women with lupus. However, its mechanism against preeclampsia remains unclear. We investigated the effect of hydroxychloroquine on an N ω -nitro-l -arginine methyl ester-induced preeclampsia rat model. Methods: Pregnant Sprague–Dawley rats were divided into four groups based on treatment (administered on gestational days 7–18): control, N ω -nitro-l -arginine methyl ester, hydroxychloroquine, and N ω -nitro-l -arginine methyl ester plus hydroxychloroquine. All animals were sacrificed on gestational day 19. We assayed tube formation and determined reactive oxygen species levels using human umbilical vein endothelial cells. Results: Results showed that hydroxychloroquine significantly lowered mean systolic blood pressure ( P < 0.05) in N ω -nitro-l -arginine methyl ester-treated rats. Hydroxychloroquine did not affect their fetal and placental weights. Hydroxychloroquine mitigated N ω -nitro-l -arginine methyl ester-associated changes in proteinuria ( P < 0.05). It normalized plasma soluble fms-like kinase-1 ( P < 0.05) and endothelin-1 ( P < 0.01) levels. In the tube formation assay, hydroxychloroquine increased the total meshes area ( P < 0.05) and mitigated N ω -nitro-l -arginine methyl ester–induced reactive oxygen species formation ( P < 0.05) in human umbilical vein endothelial cells. Conclusion: We conclude that hydroxychloroquine alleviated hypertension, proteinuria, and normalized soluble fms-like kinase-1 and endothelin-1 levels in our preeclampsia model and that these changes may involve the restoration of endothelial dysfunction; thus, hydroxychloroquine could potentially be used for preventing preeclampsia, even in the absence of lupus.